Job Standardization and Employee Voice - Mao, Hsiao-Yen; Mao, Chueh-Wei (Relations industrielles / Industrial Relations, 2023)
SummaryAn organization expects its employees to comply with job standardization to improve its production efficiency, while also expecting them to make suggestions to improve their job performance. Are the two goals compatible? Does job standardization turn employees into active speakers or stifled ones? This study is about how and why job standardization influences employee voice. I use conservation of resources (COR) theory to articulate competing hypotheses and a mediating process for the individual mechanism of employees’ role orientation in their job. In a three-wave panel survey, 232 employees completed questionnaires. The results indicate that job standardization reduces employee voice by narrowing the employee’s role orientation, in line with the resource conservation argument of COR theory. The results further suggest that job standardization is resource-depleting and causes the employee to focus on resource conservation to fulfill job requirements. The employee is less likely to consume resources and thus less likely to voice ideas and suggestions.This study shifts our understanding of employee voice from individual, interpersonal and organizational antecedents to the neglected antecedent of job characteristics. Given that the effects of job characteristics have often been explained in terms of the job itself, i.e., job characteristics theory, this study provides an alternative explanation in terms of the worker, i.e., resource theory. Organizations standardize jobs in order to improve production; in doing so, however, they create a dilemma: job standardization makes production more difficult to improve because the employees are less likely to voice their concerns. This study provides a specific, job-related way for managers to keep employee voice from being stifled or ignored. I propose that job standardization should consider the relative importance of employee voice and be classified as either discipline-related or job-content-related.AbstractAn organization expects its employees to comply with job standardization to improve its production efficiency, while also expecting them to make suggestions to improve their job performance. Are the two goals compatible? Does job standardization turn employees into active speakers or stifled ones? This study is about how and why job standardization influences employee voice. I use conservation of resources (COR) theory to articulate competing hypotheses and a mediating process for the individual mechanism of employees’ role orientation in their job. In a three-wave panel survey, 232 employees completed questionnaires. The results are consistent with the resource conservation argument of COR theory: job standardization is resource-depleting and tends to narrow the role orientation of employees, who thus focus on resource conservation to fulfill job requirements and are in turn less likely to consume resources and voice suggestions. This study provides a specific, job-related way for managers to keep employee voice from being stifled or ignored. Job standardization should consider the relative importance of employee voice and be classified as discipline-related or job-content-related.